EFFECT OF LIUIDITY, SOLVENCY AND PROFITABILITY ON THE VALUE OF THE COMPANY AT PT. INDAH KIAT PULP AND PAPER TBK - Tiara Meldiany Putri; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims partially to test the effect of liquidity, solvency, and profitability on firm value. Where the independent variables in this study are liquidity, solvency and profitability and the dependent variables is the value of the company.This research uses secondary data in the form of company financial reports and annual reports on annual reports of PT. Indah Kiat Pulp And Paper Year 2007-2018. The data analysis use simple linear regression analysis, multiple linear regression, coefficient of determination and T test test using SPSS 23 devices.The analysis shows that the partial liquidity variable (t test) affect the value of  the company at PT. Indah Kiat Pulp And Paper, partial solvency variabel (test t) negatively affect the value of the company at PT. Indah Kiat Pulp And Paper, profitability variabel (test t) does not affect the value of the company at PT. Indah Kiat Pulp And Paper. Keywords: Likuidity, Solvency, Profitability, The Value of The Company